Peran kebijakan dividen dalam memediasi kinerja keuangan terhadap return saham - Meidiyustiani, Rinny; Laksmiwati, Mia; Oktaviani, Retno Fuji; Rolanda, Ivo (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the role of dividend policy as an intervening variable of the company's financial performance which consists of the ratio of liquidity, solvency, activity and profitability to stock returns in public companies that are members of LQ 45 on the Indonesia Stock Exchange during the 2016-2021 period. The type of research is quantitative research with a descriptive approach. With purposive sampling technique, 21 companies were obtained as samples. Analysis and testing of research hypotheses using the Structural Equation Model - Partial Least Square (PLS) method, which is run with SmartPLS version 3.0 software. The results showed that liquidity and activity had an effect, but profitability and solvency had no effect on the Dividend Payout Ratio. Only solvency has an effect, while liquidity, activity and profitability have no effect on stock returns. Furthermore, the Dividend Payout Ratio has no role in mediating financial performance on stock returns.